A Antecedent Analysis Of Employee E-Hrm Effectiveness In Companies Implementing E-Hrm In Batam City - Farid, Ridhayati; Ella Triana Wirawan; Yuddy Giovanna Priscilla (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2025)
The use of